Influência da extensão da doença periodontal no perfil sanguíneo de ratos Wistar - Guimarães, Gustav [UNESP] (2016)
The aim of this study was to evaluate the influence of the periodontal disease extension on the blood profile of Wistar rats. Thirty rats were divided into 3 groups of 10 animals each: C control rats; DP1- rats with periodontal disease in 3 upper molars; DP2 - rats with periodontal disease in 3 upper and 3 lower molars. Periodontal disease was induced by ligature around the tooth according to each group. After 30 days, the animals were killed and 5ml of blood was collected for analyzes of blood count parameters, creatinine, triglycerides and cholesterol. Then the animals were sacrificed and the jaws removed and processed for histopathological analysis to characterize, in H.E. staining, the profile of periodontal disease in each animal. The results from the hematologic tissue were analyzed statistically by ANOVA and Tukey test, with 5% significance level. It can be observed in groups DP1 and DP2 presence of chronic inflammatory infiltrates, connective tissue attachment loss and alveolar bone cortical structure loss, presence of resorptions, presence of biofilm and bone sequestration. As for the blood profile, it is can observe a statistically significant difference between the control group and the groups DP1 and DP2 to the amount of leukocytes and lymphocytes (p <0.05). Further, DP2 group had a higher amount of leukocytes and neutrophils compared to DP1 and control group (p <0.05). It can be concluded that the presence of periodontal disease increases the amount of leukocytes, neutrophils, and lymphocytes in the blood of Wistar rats, and the extent of periodontal disease affects the quantification of leukocytes and neutrophils.